Reinterpreting the Diachronic Variations in the Numbers of Burials Known from Early Iron Age Athens - Rönnberg, Maximilian F. (Journal of Greek Archaeology, 2021)
The number of burials per year known from Athens decreases significantly in the Protogeometric period and then increases rapidly again in the Late Geometric period. The explanation offered for this development by Morris in 1987 is the most popular one so far. This paper will first quickly discuss this and other previous ideas and their wider implications, but then focus on providing a new one. The starting point of this new interpretation is that various types of burial sites may have different recovery rates. I will thus first sketch the different possibilities for the location of graves in Athens in the Early Iron Age and the Archaic period. The subsequent diachronic analysis of these different types of burial sites and their respective popularity forms the core of this contribution. A case study of the Kerameikos and the area of the later Agora as well as an overview of all Athenian sites is provided. These developments and their correspondences in the grave count allow for an interpretation which does account for the variations in the known numbers of graves as well as the changing spatial patterns. This is finally set into the wider field of socio-cultural changes in Early Athens.